2018
DOI: 10.1680/jgeot.16.p.266
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element analysis of arching in highway piled embankments subjected to moving vehicle loads

Abstract: This paper presents a simplified finite-element model, based on which the arching in highway piled embankments subjected to moving vehicle loads is investigated. The analyses demonstrated that the pile spacing was a more sensitive factor than embankment height, whose increase from 2·0 to 3·0 m led to a 60–68% increase of the normalised maximum settlement at the base of the embankment. The effect of moving vehicle loads was of particular interest, increasing the normalised maximum settlement and vertical stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Zhuang & Wang. [ 27 ] found that cohesion is the most sensitive factor affecting the normalised maximum settlement and vertical stress of embankment.…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang & Wang. [ 27 ] found that cohesion is the most sensitive factor affecting the normalised maximum settlement and vertical stress of embankment.…”
Section: Introductionmentioning
confidence: 99%
“…Piled embankments have been widely adopted to overcome intolerable total or differential settlements, large lateral displacements of highway, and railway engineering, especially for embankments constructed over soft soils [1][2][3][4][5][6][7][8][9]. Soil arching effect is a ubiquitous phenomenon occurred in the piled embankment to transfer the vertical stress from the relatively stiff pile to the softer soil due to the differential settlement [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these DEM simulations still attempt to identify the soil arching according to the deformation pattern of the embankment, rather than the redistributions of the stress or contact force chains [15]. Generally, the soil arching formed in the piled embankments considerably enhanced the load transfer from the relatively stiff piles to the softer subsoil [5,[12][13][14][15][16][28][29][30]36]. In this regard, this study investigated the soil arching in piled embankments with the 2D DEM modeling software, Particle Flow Code in Two Dimensions (PFC 2D ), version 5.0, developed by Itasca [37].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ground improvement techniques have been adopted to address soft subgrade‐related issues, among others: grouting [eg,], soil mixing [eg,], micropile [eg,], soil nail [eg,], stone column [eg,], and rigid inclusions . The last one (also known as column‐supported embankment) are gaining more attention every time in geotechnical engineering in general [eg,], and in the railroad industry in particular [eg,]. This increasing interest is because this soil improvement technique is based on traditional materials (eg, timber or concrete piles), which are relatively easy to access for the railroad industry.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ground improvement techniques have been adopted to address soft subgrade-related issues, among others: grouting [eg, [22][23][24][25] ], soil mixing [eg, [26][27][28][29] ], micropile [eg, [30][31][32] ], soil nail [eg, [33][34][35][36] ], stone column [eg, [37][38][39][40], and rigid inclusions. [41][42][43][44][45][46][47][48][49][50][51][52] The last one (also known as column-supported embankment) are gaining more attention every time in geotechnical engineering in general [eg, [53][54][55][56][57][58][59][60][61], and in the railroad industry in particular [eg, [62][63][64][65][66][67] ]. This increasing interest is because this soil improvement technique is based on traditional materials (eg, timber o...…”
Section: Introductionmentioning
confidence: 99%